Antimicrobial effects of stinging nettle (urtica dioica L.) extracts on campylobacter jejuni - OMURTAG KORKMAZ, BURCU İREM (My University, 2021)
Stinging nettle (Urticadioica L.) is a perennial plant from the Urticaceae family, whose leaves and stem are covered with irritating hairs. It grows wild in Europe, North America, North Africa and West Asia and in every region of our country. U. dioica; regard to its rich nutritional value and essential oils, phenolic compounds and flavonoids, has been used both as a food and traditionally for healing since years. Campylobacter jejuni is a gram-negative bacterium that causes infections especially in poultry meat, meat products, raw milk, contaminated water, and foodborne infections. It is a common cause of diarrhea cases in developing countries and sporadic gastroenteritis in developed countries around the world. C. jejuni produces adenylate cyclase activating toxin, causing "campylobacter gastroenteritis". It is also a notable pathogen in terms of infection control, due to its association with severe neuropathological sequelae such as, GuillainBarré, Reiter syndromes, and cases of bacteremia. C. jejuni, which can rapidly develop resistance to antibiotics used for infection control, poses a global risk to human health and increases the need for the development of antimicrobials with different mechanisms of action.In today's agriculture and food industry, natural and safe antimicrobials are needed with the widespread use of antibacterials and increased bacterial resistance to existing antibiotics for the control of microorganisms that pose a global health risk in the medical field. For this reason, U. dioica is often under investigation for its antimicrobial effects. In the literature, extracts of U. dioica against food-borne Campylobacter jejuni, Pseudomonas, Shigella spp., Bacillus cereus, Staphylococcus aureus, Vibrio parahaemolyticus, and Escherichia coli; hospital acquired, Staphylococcus aureus, Bacillus subtilis, Salmonella spp. and there are data showing antimicrobial activity on methicillin-resistant Staphylococcus auerus (MRSA). In disk diffusion analysis, it was found that U. dioica ethanolic extract exhibited antimicrobial effects on C. jejuni. It has been determined that tinctures of U. dioica have a minimum inhibitory concentration of 3.125% against C. jejuni. By using U. dioica extract as a strategy to combat infections, it seems to be important revealing its potential of inhibition
Keywords: Urtica dioica; nettle; antimicrobial agents; Campylobacter jejuni